A commentary on "First-hand experience of accessible information". Issue 2 (7th April 2015) - Unknown
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to provide a commentary on Mander's paper on people with learning disabilities' first-hand experience of accessible information. Design/methodology/approach – The commentary reflects on some of the findings presented by Mander and builds on these, with particular emphasis on what it means to understand information. Findings – Everything from initial product design to building capacity and constructing knowledge requires expertise and attention to detail. Originality/value – There are no easy fix solutions to achieving understanding of information for people who have learning disabilities.